Analysis of the full-day school model education program in primary schools in Maybrat Regency - Frasawi, Hendrik; Wawointana, Thelma; Kairupan, Sisca B. (Technium Social Sciences Journal, 2025)
This study aims to describe and analyse the implementation of the Full Day School Model Education Program (SSH) in primary schools in Maybrat Regency. This research used a descriptive qualitative approach with 10 predetermined informants. The data collection techniques used included observation, interviews and documentation. The data obtained were analyzed through the stages of data reduction, data presentation, and conclusion drawing and verification. Based on the results of the study, it was found that the implementation of this program has not fully run optimally due to various challenges, such as limited facilities and infrastructure, low student participation rates, inadequate safety and comfort of learning, suboptimal education standards, and various community responses to this program. Then, this study identified several determinant factors that became the main obstacles in the implementation of SSH education model. These factors include ineffective communication between government, schools and communities; limited budgets and physical facilities that do not support learning; lack of ongoing training for teachers; suboptimal time management; and weak coordination between various stakeholders. As a solution, this study recommends several concrete steps, including improving facilities and infrastructure with greater budget support, increasing student and parent participation through the provision of better transportation and communication, improving the safety and comfort of the school environment, and developing a more balanced learning schedule. In addition, increased coordination between related parties and optimization of needs-based policies in the field are also key factors in improving the effectiveness of SSH education model implementation in Maybrat Regency.